Pemanfaatan Susu Tempe Pada Program Antenatal Care (Anc) Terpadu oleh Ibu Hamil pada Masyarakatdesa Klaseman Kecamatan Gending Kabupaten Probolinggo - Verto Septiandika (Abdi Panca Marga, 2019)
Antenatal Care (ANC) is a health service by trained health workers for mothers during their pregnancy according to the service standards established in the Midwifery Service Standards (SPK). This service aims to find out the results of the use of tempe milk findings in ANC activities in the Klaseman Village, Gending District, Probolinggo Regency. The results of the implementation of this activity showed that there were 14 pregnant women who made use of the ANC. Found one miscarriage pregnant women, one pregnant woman gave birth, 4 people experienced tartar, 5 people experienced a high risk, and 2 people experienced a very high risk. In carrying out this ANC activity, we also found findings in the form of products to combat stunting in Des Klaseman. It is expected that the Puskesmas and Klaseman Village apparatus will improve counseling on the benefits and objectives of ANC examinations, the importance of regulating birth spacing, the ANC services that Puskesmas can provide, changing perspectives, attending training and involving traditional birth attendants and community leaders. The goal of providing information is extended to families / husbands because their support has a real influence on the use of ANC. Keywords: Antenatal care, knowledge, support of health workers, Solutions, trust.